Tunable electroluminescence from an n-ZnO/p-GaN heterojunction with a CsPbBr3 interlayer grown by pulsed laser deposition. Issue 35 (17th August 2020) - Huang, Yu; Zhou, Xiaoyu; Zhang, Lichun; Lin, Guochen; Xu, Man; Zhao, Yuan; Jiao, Mengmeng; Zhang, Dengying; Pan, Bingying; Zhu, Linwei; Zhao, Fengzhou
Abstract : Heterojunction light-emitting diodes (LEDs) based on n-ZnO/CsPbBr3 /p-GaN have been fabricated by using pulsed laser deposition (PLD). Abstract : Heterojunction light-emitting diodes (LED) based on n-ZnO/CsPbBr3 /p-GaN have been fabricated by using pulsed laser deposition (PLD). The effects of the CsPbBr3 interlayer on the electroluminescence (EL) performance of n-ZnO/p-GaN have been systematically studied. It was found that the CsPbBr3 interlayer plays an important role in the emission performance of the heterojunction LED. By adjusting the thickness of CsPbBr3, the emission peaks of the heterojunction LED change from violet to greenish-yellow, indicating that the electroluminescence characters can be tuned by the CsPbBr3 film thickness. Detailed emission mechanisms influenced by the CsPbBr3 film have been investigated using the Anderson band diagram. The results provide a new method for the fabrication of single-chip white LEDs.